Media Loose Parts dalam Menstimulasi Keaksaraan Awal Anak Kelompok A di TK Baik Krapyak: Loose Parts Media in Stimulating Early Literacy Group A Children in Kindergarten Baik Krapyak - Iftitahul Husniyati Arramdhani (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
Early childhood learning activities have the principle of learning while playing. The play tools used are usually real so that you can learn about shape, size, color, and so on. One media that can support children's early literacy stimulation is loose parts media. Loosaparta is a natural, used or artificial material that can be combined from one material with another, so that children can learn concretely. The research aims to describe looseparts media in stimulating early literacy for group A children at Kindergarten BAIK. This type of research is qualitative research with a case study approach. Data collection techniques were obtained from classes Al and A2 by observing learning activities, interviews and documentation. Checking the validity of the data was carried out using the triangulation techniquel. The results of the research show that looseparts stimulates early literacy in group A children at Kindergarten BAIK by carrying out all stages of using looseparts. The first stage of the teacher is edukası (conveying the topic) the child is in the exploration stage (exploringı) The second stage of the teacher is expansion (invitation and provocation) the second stage of the child is experimentation (trying out), the third stage of the child is creative (exploring the material) the teacher is in development stage (documentation), the fourth stage is carried out by children together with the teacher, namely building the meaning and purpose of play (reviewing).   ABSTRAK Kegiatan belajar anak usia dini memiliki prinsip belajar sambil bermain. Alat permainan yang digunakan biasanya berbentuk nyata sehingga dapat belajar mengenai bentuk, ukuran, warna, dan sebagainya. Salah satu media yang dapat mendukung untuk menstimulasi keaksaraan awal anak adalah dengan media looseparts. Looseparts merupakan bahan alam, bekas, maupun buatan yang dapat dikombinasikan dari satu bahan dengan bahan lain, sehingga anak dapat belajar secara konkrit. Penelitian ini bertujuan untuk mendeskripsikan media looseparts dalam menstimulasi keaksaraan awal untuk anak kelompok A di TK BAIK. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data diperoleh dari kelas A1 dan A2 dengan melakukan observasi kegiatan pembelajaran, wawancara, dan dokumentasi. Pemeriksaan keabsahan data dilakukan dengan teknik triangulasi. Hasil penelitian menunjukan bahwa looseparts dalam menstimulasi keaksaraan awal anak kelompok A di TK BAIK dilaksanakan dengan melakukan seluruh tahapan penggunaan looseparts. Tahap pertama guru adalah edukasi (menyampaikan topik) anak berada pada tahap eksplorasi (menjelajahi). Tahap kedua guru adalah ekspansi (invitasi dan provokasi) tahap kedua anak yaitu eksperimen (mencoba-coba), tahap ketiga anak yaitu kreatif (mengeksplor bahan) guru berada pada tahap perkembangan (dokumentasi), tahap keempat dilakukan anak bersama guru yaitu membangun makna dan tujuan bermain (mereview).